Aspectos epidemiológicos, clínico-patológicos e genéticos de parvovírus canino tipo 2 (CPV-2) no Rio Grande do Sul, Brasil - Oliveira, Pablo Sebastian Britto de (2019)
Canine parvovirus type 2 CPV-2 is considered the most important agent of enteritis in dogs. CPV-2 has undergone a rapid genetic evolution, mainly due to mutations in the major capsid protein (VP2) gene, whose product is involved in the binding of the virions to cellular receptors and is a major target for neutralizing antibodies. Mutations in VP2 were responsible for the emergence of viral variants (CPV-2a, 2b and 2c) that may induce distinct clinical-pathological manifestations in the host. Thus, this study aimed to describe the epidemiological, clinical and pathological aspects of cases of gastroenteric disease associated with CPV-2c infection and to analyze the complete sequence of the VP2 gene of CPV-2 samples obtained from dogs with clinical parvovirosis in Rio Grande do Sul, Brazil. The first study describes the the epidemiological and clinico-pathological findings of 24 cases of gastroenteritis by CPV-2, followed by partial nucleotide sequencing and analysis of VP2. Signs and/or lesions suggestive of parvovirus enteritis were reported in most cases, including diarrhea, vomiting, small intestinal serous membrane hemorrhage, diffuse segmental granulation, villous atrophy, crypt necrosis and fusion, squamous metaplasia and epithelial synechia. However, some cases presented aspects distinct from classical parvovirosis, such as feces/diarrhea collor (reddish and/or yellowish, light brown, brownish or brownish), extensive involvement of the small intestine (8/20), presence of pulmonary edema (7/24), seizures (3/24), involvement of adult dogs (4/24) and vaccinated animals (12/24). Virus isolation in cell culture was achieved from 58.3% (14/24) of the samples. Nucleotide sequencing revealed a high nucleotide identity in VP2 (99.4-100%), as well as the presence of glutamic acid at residue 426, characterizing the isolates as CPV-2c. In the second study, 38 fecal samples or intestinal segments of dogs with gastroenteritis were submitted to CPV-2 detection and sequence analysis of VP2. Analysis of amino acids 87, 101, 297, 300, 305 and 426 allowed for the identification of 20 isolates/viruses as CPV-2c, four as CPV-2b, 11 as New CPV-2a, two as New CPV-2b and one as CPV- like. CPV-2c sequences were characterized by high amino acid similarity. New CPV-2a and New CPV-2b genomes were characterized by an alanine at residue 297 (Ser297Ala), but only the New CPV-2a sequences showed the Phe267Tyr, Tyr324Ile and Thr440Ala mutations that are associated with the development of the disease in vaccinated dogs. The SV726/15 virus was classified as CPV-2-like since it harbored some mutations similar to the original CPV-2, such as Leu, Thr, Ala and Asp at residues 87, 101, 300 and 305, respectively. Such mutations in CPV-2-like indicate a re-emergence and/or evolution of CPV-2 from vaccine strains. At phylogenetic analysis, the variants grouped together with the respective reference strains, in general, according to the changes observed in amino acids sequences. The results obtained in these studies demonstrate that CPV-2c circulates in dog populations from RS, often inducing epidemiological and clinic-pathological manifestations distinct of the classical parvovirosis. Furthermore, sequence analysis of CPV-2 samples demonstrates the high diversity in the VP2 gene of viruses circulating in the canine population in southern Brazil with the consequent emergence of new variants.